2020
DOI: 10.21203/rs.3.rs-29105/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Association Between Male Infertility and Cardiometabolic Disturbances: A Population Based Study

Abstract: Aim: Studies focusing of male infertility and cardio-metabolic disorders is insufficient and controversial. The aim of this study was to evaluate the association between male infertility and cardiometabolic disturbances in a population based Tehran lipid and glucose study. Material and methods: For the purpose of the present study, we used data collected in 3rd follow up visit of Tehran Lipid and Glucose Study, which included comprehensive data on reproductive status of participants. All those who were never m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The authors concluded that medical comorbidities are associated with impaired sperm production and suggested that male infertility evaluation offers not only specific therapy to improve semen parameters but also treatment for non-specific medical comorbidities, which may benefit general health status and spermatogenesis restoration. Several other population-based studies have shown the association between male infertility and hypertension (125)(126)(127). Animal studies have also thrived in this aspect of reproductive research and have provided evidence that hypertension is associated to male infertility (128)(129)(130).…”
Section: Hypertension-induced Os In Male Infertilitymentioning
confidence: 99%
“…The authors concluded that medical comorbidities are associated with impaired sperm production and suggested that male infertility evaluation offers not only specific therapy to improve semen parameters but also treatment for non-specific medical comorbidities, which may benefit general health status and spermatogenesis restoration. Several other population-based studies have shown the association between male infertility and hypertension (125)(126)(127). Animal studies have also thrived in this aspect of reproductive research and have provided evidence that hypertension is associated to male infertility (128)(129)(130).…”
Section: Hypertension-induced Os In Male Infertilitymentioning
confidence: 99%
“…We identified 27 full text articles to reevaluate after screening the titles and abstracts. Ultimately, seven published articles involving 102,152 infertile men were included in this review (Behboudi‐Gandevani et al, 2021; Bungum et al, 2018; Cazzaniga et al, 2020; Eisenberg et al, 2015, 2016; Elenkov & Al‐Jebari, 2018; Kasman et al, 2019) (Figure 1). Table 1 summarizes the main characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, although many studies have focused on the impact of male infertility on hypertension, their results still conflict. Some studies have indicated that male infertility is significantly associated with hypertension risk (Eisenberg et al, 2015; Kasman et al, 2019), whereas others have reported no such association (Behboudi‐Gandevani et al, 2021; Bungum et al, 2018; Cazzaniga et al, 2020). To address this issue, we conducted a meta‐analysis and systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…A few authors investigated the association between prediabetes, semen and male sexual hormone parameters. A recent study 81 investigating 88 men with male infertility and 1523 men with at least one live birth reported no association between infertility and prediabetes.…”
Section: Prediabetes Semen and Male Sexual Hormone Parametersmentioning
confidence: 94%
“…A few authors investigated the association between prediabetes, semen and male sexual hormone parameters. A recent study 81 investigating 88 men with male infertility and 1523 men with at least one live birth reported no association between infertility and prediabetes. However, another recent study 82 investigating 744 men with primary infertility aged between 19 and 50 years reported a prevalence of prediabetes in infertile men of 15.4% and some infertility‐related abnormalities associated with prediabetes (see below).…”
Section: Prediabetes Semen and Male Sexual Hormone Parametersmentioning
confidence: 94%